Implementation of Active Listening Techniques in Arabic Language Learning at Islamic Senior High Schools: Teachers’ and Students’ Perspectives - Iis Puspita Dewi; M. Akmal Anshory; Salsabila Zahro Nurul Aufa (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the implementation of active listening techniques in Arabic language learning at Islamic Senior High Schools (MA) from the teachers’ perspective; students’ experiences and perceptions of the implementation of active listening techniques; the supporting and inhibiting factors in applying active listening techniques according to both teachers and students; and the impact of these techniques on students’ comprehension of Arabic listening skills at MA. This research employs a descriptive qualitative approach to provide an in-depth depiction of the implementation of active listening techniques in Arabic language learning at MA. Primary data were obtained through observations, interviews, and direct interactions with teachers and students, while secondary data were sourced from instructional documents and relevant literature. Data collection was conducted through classroom observations, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, to produce a comprehensive understanding of active listening practices. The findings indicate that the implementation of active listening techniques at MA is carried out through three stages using strategies such as vocabulary activation, identification of key words, clarification, reflection pauses, and paraphrasing. These techniques help students remain focused, understand audio materials progressively, and engage more confidently in discussions. However, limitations in vocabulary mastery, audio speed, facilities, and time constraints serve as inhibiting factors. Learning motivation, a communicative classroom atmosphere, and teacher readiness support successful implementation. Overall, the technique positively impacts students’ comprehension and learning motivation.